Pengaruh Bauran Pemasaran Terhadap Keputusan Pembelian Smarphone Merek Samsung Berbasis Android (Studi Pada Mahasiswa Administrasi Bisnis Fakultas Komunikasi Dan Bisnis Angkatan Tahun 2010-2013) - Dara Patria Harjasiswi; Ai Lili Yuliati (Jurnal Studi Manajemen dan Bisnis, 2014)
This study aims to determine the effect of the marketing mix on consumer purchasing decisions on students of the Faculty of Business Administration and Business Communications force from 2010 to 2013. The method used is a quantitative method to study a type of descriptive research and causal. Types of data required for the study is primary data and secondary data. While the techniques used in collecting data for the study were interviews, questionnaires, and literature study. Sampling was done by the method of non- accidental sampling probabilty sampling type, the number of respondents of 100 respondents. Then, for data analysis used descriptive analysis and multiple linear regression analysis.Based on the results of data processing multiple linear regression analysis, marketing mix simultaneously positive and significant impact on consumer purchasing decisions a student of Business Administration at the Faculty of Communication and Business class 2010-2013. Based on the results of the test of the hypothesis partially obtained variable product and place a positive and significant impact on consumer purchasing decisions a student of Business Administration at the Faculty of Communication and Business class 2010-2013. While variable price a negative and not significant impact, and variable promotion a positive but not significant impact. Based on the coefficient of determination obtained that the marketing mix is able to explain the purchase decision by 35.2% and the remaining 64.8% were influenced by other factors such as personal factors (Sari, 2013:35), or other factors not examined in this study, so it needs to be explored regarding the other factors in their influence on purchasing decisions based Samsung android smartphone. This reform should be linked to the vision and strategy of the company as well as tailored to the ability of the company, so the company is able to determine priorities for improvement.